Չինաստանի էներգետիկ անվտանգության գործոնը միջազգային գործընթացների համատեքստում - Սաֆարյան, Մնացական; Բաղդասարյան, Սուրեն («Զանգակ - 97»)
This paper discusses the issues of China's energy security under the light of the strcngthening international competition for the hydrocarbons, which assumes Strategie importance for all big international actors, and especially for China. Here are considered some of the aspects of international politics that came into light by the rapid change of world с rüde oil demand and supply equilibrium, and the implieations thereupon. A special attention is paid to the issue of the energy security of China as one of the decisive factors of today's world economy and world politics. Describing the current trends in oil and natural gas market, the relations of China in energy area with its major partners, the authors come to a conclusion that China is seriously concemcd with the issue of its own security energy and will continuously make futher efforts to secure stable supply of oil necessary to satisfy the country's growing economy. The paper also considers some of the repercussions of these processes on South Caucasus.
Keywords: Տնտեսություն; Պատմություն; Չինաստան